Assessment of the stunning method and short lairage time on the carcass and pork quality traits - Jerez-Timaure, Nancy (2020)
The effect of short lairage time (SLT: ≤1h and 3 h) and two stunning methods – SM (electrical and gas) and their interaction on carcass and pork quality was evaluated. The study was carried out with 108 barrow male pigs weighing 95-100 kg. Carcass defects (ecchymosis-petechiae, bruises, bone/muscle separation in the pork chop loins and bone fractures) and meat quality traits: pH45min, pH24h, color, water holding capacity (WHC), and drip loss (DL) were determined. The SLT affected WHC (p<0.05), where the meat from animals with SLT <1h had higher water losses (24.6%) when compared to those from animals with SLT = 3h (21.3%) (p<0.05). The electrical SM caused more carcass defects (bruises, bone separation in the pork chop loins and bone fractures in pork chops) and lower WHC value (p<0.05). The bone fractures were found in a higher incidence in carcasses from electrical SM with minimal lairage time and electrical SM with 3 h of SLT. The electrical SM caused a higher incidence of carcass defects and lower WHC. The electrical SM was more predisposed to produce an incidence of defects in the carcass, in the quality of the carcass and pig meat, while the SLT treatments did not cause significant variations neither in the carcass defects nor in the quality of the meat.